Gastro-Poetics in Lithuanian Yiddish Literature of the Interwar Period: The Early Work of Moyshe Kulbak (1896-1937) - Leitane, Iveta (Colloquia, 2022)
For almost a hundred years, literary critics and scholars have been trying to reach the depths of Moses Kulbak’s work and find the most appropriate keys to interpreting his sophisticated and puzzling works. This article is an attempt to approach author’s work by focusing on seemingly less important details and reconstructing their relational network. The depiction of eating scenes, meals (including ruined and imagined ones), as well as food and drink have been chosen as focus point. Such strategy, emphasizing body in the humanities, allows to draw attention to other key issues, such as the relationship between body and soul, nourishment and intellect, intellect and faith, etc. The article deals with the first decade Kulbak’s work and examines less discussed sources of inspiration of the great Yiddish poet and prose writer. Using metric and semantic analysis, the place and role of eating habits, meal scenes and spectacular food representations in Kulbak’s poetic universe are explained and reconstructed. Food metaphors help uncover hidden interconnections, and although they often play only a connotative role, they are still powerful means for expressing the author’s message, while simultaneously concealing it.